МЕТРОЛОГІЧНЕ ЗАБЕЗПЕЧЕННЯ ФАЗОВИХ ВИМІРЮВАНЬ В ЛАЗЕРНІЙ ДАЛЕКОМЕТРІЇ - Брагинець, І.О.; Масюренко, Ю.О. (Інститут електродинаміки НАН України, Київ, 2025)
The relevance of developing precision two-channel signal phase shift calibrators (SFCs) in a wide frequency range for experimental assessment of hardware errors of phase measuring devices of laser rangefinders is confirmed. The possibility of constructing a SFC based on widespread direct digital synthesis frequency synthesizers is considered. It is shown that in the range of high and very high frequencies, which is typical for signals in phase laser rangefinders, the specified SFCs, due to parasitic couplings between the channel circuits, do not provide the required accuracy of reproducing the phase shift between two sinusoidal voltages. To increase the accuracy, it is proposed to transfer the formation of signals in the SFCs to the optical range of electromagnetic waves. The principle of constructing the corresponding SFCs is described and a scheme for its practical implementation is developed. The calculation of the possible error of the proposed SFCs is carried out, the result of which confirms the feasibility of its use for research and testing of phase measuring devices of high-precision laser rangefinders. References 10, figures 1.